Quality of democracy and institutional performance in Chile. A retrospective analysis based on Sebastián Piñera’s government program - Avendaño, Octavio (Política. Revista de Ciencia Política, 2011)
This paper analyzes recent experiences of Chilean democracy, from a quality perspective. To do so, the analysis prioritizes procedural dimensions, in particular those that combine political participation and competition with accountability processes that derive from specialized state bodies, and particularly from representative institutions. It is assumed that dimensions linked to the system of representation and intermediation that determine the success and effectiveness of procedural and substantive dimensions. It is concluded that in the current government’s proposals for democratic deepening there are a number of gaps and omissions regarding relevant and substantive topics.